2020
DOI: 10.1017/s2045796020000633
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity within mental disorders: a comprehensive analysis based on 145 990 survey respondents from 27 countries

Abstract: Aims Epidemiological studies indicate that individuals with one type of mental disorder have an increased risk of subsequently developing other types of mental disorders. This study aimed to undertake a comprehensive analysis of pair-wise lifetime comorbidity across a range of common mental disorders based on a diverse range of population-based surveys. Methods The WHO World Mental Health (WMH) surveys assessed 145 990 adult respondents from 27 countries. Based on retrospectively-reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
69
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 19 publications
(24 reference statements)
10
69
0
1
Order By: Relevance
“…In some disorder pairs (e.g., MOOD and GAD), the pooled estimate was as high as 19 times (aOR = 18.7). However, our estimates were broadly consistent with two studies that were published after the completion of our data extraction: a large register‐based study from Denmark ( n = 5 940 778) (Plana‐Ripoll et al, 2019), and a trans‐national analysis that combined individual data from 27 countries ( n = 145 990 survey respondents) (McGrath et al, 2020). Overall, the consistent patterns identified by our systematic review, and the findings from these two recent studies, provide convergent evidence of the strong comorbidity between these disorders.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In some disorder pairs (e.g., MOOD and GAD), the pooled estimate was as high as 19 times (aOR = 18.7). However, our estimates were broadly consistent with two studies that were published after the completion of our data extraction: a large register‐based study from Denmark ( n = 5 940 778) (Plana‐Ripoll et al, 2019), and a trans‐national analysis that combined individual data from 27 countries ( n = 145 990 survey respondents) (McGrath et al, 2020). Overall, the consistent patterns identified by our systematic review, and the findings from these two recent studies, provide convergent evidence of the strong comorbidity between these disorders.…”
Section: Discussionsupporting
confidence: 86%
“…However, these estimates were based on a limited number of studies. Although this bidirectional association was broadly consistent with our recently conducted population‐based studies (McGrath et al, 2020; Plana‐Ripoll et al, 2019), there was a lack of consistency between these studies regarding the symmetry between the size of the reciprocal risk estimates (i.e., did the effect sizes differ according to order, regardless of the fact that both estimates were substantially above 1 and significant). Bi‐directionality within pairs of comorbid disorders suggests that these disorders may result from shared underlying risk factors (e.g., genetic; Levey et al, 2020; Purves et al, 2019; and/or shared early life exposures; Kessler et al, 1997).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this pilot study of a small case series, we found evidence that about 21% could be viewed as having a poor clinical outcome with 7% of participants (one individual) developing BD, 7% a psychotic disorder, and 7% continuing to experience mood problems, but without transition to full-threshold BD (or perhaps transition has been delayed). It is recognized that individuals who do not show transition from subthreshold to full-threshold disorders are not necessarily well, and many continue to experience a range of clinical and social impairments ( 4 , 6 , 7 ). As such, it is encouraging that 43% of the case series (six individuals) were known to be well enough to be fully discharged from mental health care.…”
Section: Resultsmentioning
confidence: 99%
“…To date, most interventions have been “disorder-specific” aiming to reduce or delay onsets of full-threshold episodes of a particular diagnosis. However, it is debatable whether a pure “disorder-specific” strategy is the best option as longitudinal and concurrent comorbidity among psychotic and mood disorders is the rule rather than the exception in youth ( 2 ) and those with onsets by age 20 have the greatest risk of developing other mental disorders over the following 15 years ( 3 , 4 ). Furthermore, subthreshold psychotic, depressive or bipolar syndromes show both homotypic continuity (continuity to the full-threshold disorder most similar to the subthreshold condition) and heterotypic continuity (transition to a different full-threshold disorder) ( 5 ).…”
Section: Introductionmentioning
confidence: 99%